Comparison of Magnetic Resonance Imaging and Stress Radiographs in the Evaluation of Chronic Lateral Ankle Instability. (April 2017) - Jolman, Scott; Robbins, Justin; Lewis, Laura; Wilkes, Melissa; Ryan, Paul
Background: In patients who develop chronic ankle instability, clinicians often obtain magnetic resonance imaging (MRI) as part of the evaluation prior to operative referral. The purpose of this study was to analyze the diagnostic efficacy of MRI in the diagnosis of chronic lateral ankle instability. Our hypothesis was that magnetic resonance imaging would not be a specific diagnostic tool in the evaluation of chronic lateral ankle instability. Materials and Methods: A retrospective chart review of 187 consecutive patients (190 ankles) was performed. Inclusion criteria for the study group required a primary complaint of instability that required operative repair or reconstruction, a documented clinical evaluation consistent with instability, stress radiographs, and MRI. Stress radiographs and clinical examinations for the study group and a control group were reviewed independently by both a musculoskeletal radiologist and a board-certified orthopaedic foot and ankle surgeon. Predictive values in terms of sensitivity, specificity, and prevalence were performed. In total, 112 patients (115 ankles) were identified who underwent an operative reconstruction of their lateral ligaments with a history, physical examination, and stress radiographs consistent with lateral ankle instability. A control group was selected consisting of 75 patients seen in the foot and ankle clinic with a diagnosis other than lateral ankle instability. Thirty-seven of the patients in the control group had stress radiographs performed in the clinic to rule out instability as part of their evaluation, and this allowed for an evaluation of the efficacy of stress radiographs in addition to MRI. Statistical analysis was performed using predictive values from sensitivity, specificity, and prevalence. Results: The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) in regards to MRI in the evaluation of patients found to have clinical lateral ankle instability and those who did not had statistical significance. Sensitivity of MRI was 82.6%, specificity was 53.3%, NPV was 66.7%, and PPV was 73%. Since 37 patients in the control group also had stress radiographs, a subanalysis was performed to identify the same values with stress radiographs. Sensitivity, specificity, NPV, and PPV were 66%, 97%, 48%, and 98.7%, respectively. The overall accuracy within this study was 71% for MRI and 74% for stress radiographs. Conclusion: This study demonstrated that MRI has high sensitivity but low specificity in the evaluation of clinical ankle instability. While MRI has value as a screening tool for concomitant ankle pathology, it should not be considered diagnostic in terms of lateral ankle instability. Level of Evidence: Level III, retrospective cohort, comparative series.